1978
DOI: 10.1093/jn/108.8.1322
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Calcium Transport Systems in Laying Hens to Exogenous and Endogenous Changes in Vitamin D Status

Abstract: Changes in intestinal calcium absorption, calcium deposition into egg shell, and intestinal, renal and uterine calcium-binding protein (CaBP) in laying hens were related to changes in 25 hydroxycholecalciferol-1-hydroxylase activity (1-hydroxylase), or to the supplementation of 1alpha-hydroxycholecalciferol (1alpha-OH-CC). The onset of egg production resulted in an increased kidney 1-hydroxylase activity and intestinal and uterine CaBP. Renal concentrations of CaBP remained unchanged. Intestinal calcium and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Corradino et al (1968) reported that the hen uterus produces calcium-binding protein in response to cholecalciferol and that electrophoretic and gelfiltration mobilities of the protein are identical with those of chick intestinal calcium-binding protein. Bar & Hurwitz (1975) and Bar et al (1978), however, demonstrated that uterine concentration of calciumbinding protein did not change in laying hens during the diurnal laying cycle and that the administration of la (OH)D3 to laying hens did not affect the content of uterine calcium-binding protein despite the marked increase in intestinal calcium-binding protein.…”
Section: Discussionmentioning
confidence: 89%
“…Corradino et al (1968) reported that the hen uterus produces calcium-binding protein in response to cholecalciferol and that electrophoretic and gelfiltration mobilities of the protein are identical with those of chick intestinal calcium-binding protein. Bar & Hurwitz (1975) and Bar et al (1978), however, demonstrated that uterine concentration of calciumbinding protein did not change in laying hens during the diurnal laying cycle and that the administration of la (OH)D3 to laying hens did not affect the content of uterine calcium-binding protein despite the marked increase in intestinal calcium-binding protein.…”
Section: Discussionmentioning
confidence: 89%
“…Characterization of CYP27B1 or a functional equivalent would provide valuable insights into ways that vitamin D 3 metabolism could be harnessed to improve eggshell integrity and skeletal welfare in layers, including using selection strategies for hens that exhibit stronger bones and eggshells. Furthermore, the influence of 1,25(OH) 2 D 3 on shell gland calcium transport has been questioned due to unresponsiveness of typical 1,25(OH) 2 D 3 -dependent proteins ( Bar et al, 1977 ; Bar, 2008 ); additional studies are needed to confirm if this applies to other aspects of shell gland calcium transport. This is especially important, as regulation of ionic calcium transfer into the shell gland lumen is poorly understood ( Nys et al, 2022 ) despite it being a limiting factor in calcium supply to the eggshell ( Cohen et al, 1978 ), so alterations in this process with age likely contribute to decreased shell quality in older hens.…”
Section: Discussionmentioning
confidence: 99%
“…Not all tissues respond to 1,25(OH) 2 D 3 in the same way. For example, shell gland calbindin D-28k ( CALB1 ) expression does not appear to be influenced by 1,25(OH) 2 D 3 ( Bar et al, 1977 ), unlike that in the kidney and small intestine ( Taylor and Wasserman, 1972 ). It may be under the control of estrogen ( Nys et al, 1992 ; Corradino et al, 1993 ), driven by half-palindromic estrogen response elements in the CALB1 promoter as has been shown in mice ( Gill and Christakos, 1995 ), and intracellular calcium levels ( Corradino, 1993 ).…”
Section: Vitamin D 3 Metabolism and Mechanism Of A...mentioning
confidence: 99%